The Youngbloods. Get Together. Hypercoagulation, Complement, and NET Formation in HIV/SIV Pathogenesis - Reno, Theresa A.; Tarnus, Lilas; Tracy, Russell; Landay, Alan L.; Sereti, Irini; Apetrei, Cristian; Pandrea, Ivona (Frontiers in Virology, 2022)
Chronic, systemic adaptive T-cell immune activation/innate inflammation (IA/INFL) were reported in persons with HIV (PWH) since the inception of the pandemic. IA/INFL also persists in PWH on antiretroviral therapy (ART), despite viral suppression. These features are recapitulated by the SIV infection of macaques. Robust proof that IA/INFL are major players in HIV disease progression and serious non-AIDS events (SNAEs) comes from studies in African nonhuman primates (NHPs) that are natural hosts of SIVs, which do not progress to AIDS despite persistent high viral replication and severe acute CD4+ T-cell loss. In these species, control of IA/INFL occurs through the maintenance of the mucosal barrier integrity, resulting in robust immune restoration during chronic infection, and absence of SNAEs. Residual IA/INFL in subjects on ART is linked to increased susceptibility of PWH to SNAEs and therefore, it should be therapeutically targeted. The origin of the HIV-associated IA/INFL is however multifactorial, including the virus itself, persistent gut dysfunction, coinfections with other pathogens (CMV, HCV, HBV), proinflammatory lipids, ART toxicity, comorbidities and behavioral factors (diet, smoking and alcohol use). Other mechanisms may also significantly contribute to IA/INFL during HIV/SIV infection and could be therapeutically targeted, but they are not completely understood. Notably, a hypercoagulable state, characterized by elevated coagulation biomarkers, including D-dimer and tissue factor, is described in HIV/SIV infection, and can accurately identify patients at risk for thromboembolic events and death. Coagulation biomarkers are highly correlated with INFL and can predict the risk of SNAE-induced end organ damage. Meanwhile, the complement system is also involved in the pathogenesis of HIV comorbidities. Despite prolonged viral suppression, ART-treated patients have high plasma levels of the proinflammatory complement protein C3a. HIV/SIV infections also trigger neutrophil extracellular traps (NETs) formation that contribute to the elimination of viral particles and infected CD4+ T-cells. However, as SIV infection progresses, generation of NETs become excessive, fueling IA/INFL and destruction of multiple immune cell subsets, and promoting microthrombotic events responsible for further tissue damages and SNAEs. Therapeutics targeting hypercoagulation, and excessive NETosis and complement activation could therefore limit persistent IA/INFL in PWH and prevent their deleterious impact on multiple organ systems.